A Randomized Trial of Direct Instruction Language for Learning in Children With Autism Spectrum Disorder - Scahill, Lawrence; Shillingsburg, M Alice; Ousley, Opal; Pileggi, Moira L; Kilbourne, Rebecca L; Buckley, Derianne; Gillespie, Scott E; McCracken, Courtney (Journal of the American Academy of Child and Adolescent Psychiatry, 2022)
To compare Direct Instruction Language for Learning (DI) plus treatment as usual (TAU) with TAU alone in children with autism spectrum disorder and moderate language delay. In this study, 83 children (age range, 4 years to 7 years 11 months) were randomly assigned to DI+TAU (n = 42) or TAU (n = 41) for 6 months. Trained therapists delivered DI in twice-weekly, 90-minute sessions for 24 weeks. The primary outcome was the standard score on the age-appropriate version of the Clinical Evaluation of Language Fundamentals (CELF). The key secondary measure was the proportion of children rated by a clinician blinded to treatment as "much improved" or "very much improved" on the Clinical Global Impressions-Improvement (CGI-I) scale. Attrition was 12%. At end point, DI+TAU participants showed a 4.8-point (8.1%) increase on CELF vs 2.3 points (4.1%) in TAU participants (difference = 2.55, p = .14, effect size = 0.25), rendering this a negative trial on the prespecified primary outcome. In post hoc analysis that adjusted for IQ, mean difference was 3.5 (p = .04, effect size = 0.33). On CGI-I, 54.8% (23/42) of DI+TAU participants were rated much improved or very much improved compared with 21.9% (9/41) of TAU participants (χ = 9.4, p = .002). On the clinically meaningful threshold of >5 points on CELF, 55.5% of DI+TAU participants achieved this benchmark vs 29.3% of TAU participants (χ = 3.6, p = .06). Complete CELF data were available for 72 participants. In the combined sample, baseline CELF scores ≤50 were associated with no improvement. On CELF, DI+TAU did not meet the prespecified difference from TAU. When adjusted for IQ, DI+TAU was superior to TAU on CELF at end point. DI+TAU was superior to TAU on CGI-I. Direct Instruction Language for Learning in Autism Spectrum Disorder; https://clinicaltrials.gov/; NCT02483910.